The Hahn Sequence Space of Fuzzy Numbers Defined by a Modulus Function - A. Pandiarani (International Journal of Mathematics And its Applications, 2016)
In this article we introduce new sequence spaces $h(F,f)$,$h_{∞}(F,f)$ and $h_{p} (F,f,s)$ of sequence of fuzzy numbers defined by a modulus function. Further some inclusion relations regarding these spaces are studied.